2018
DOI: 10.1139/apnm-2017-0578
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein concentrate supplementation protects rat brain against aging-induced oxidative stress and neurodegeneration

Abstract: Whey protein concentrate (WPC) is a rich source of sulfur-containing amino acids and is consumed as a functional food, incorporating a wide range of nutritional attributes. The purpose of this study is to evaluate the neuroprotective effect of WPC on rat brain during aging. Young (4 months) and old (24 months) male Wistar rats were supplemented with WPC (300 mg/kg body weight) for 28 days. Biomarkers of oxidative stress and antioxidant capacity in terms of ferric reducing antioxidant potential (FRAP), lipid hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…The present study was designed to test the hypothesis that WPC supplementation can improve biomolecular damage, and restore the activity of membrane transporters during aging in rats. The present study is also important in view of our recent report of antiaging and neuroprotective effect of WPC in rat brain (Garg, Singh, Singh, & Rizvi, ).…”
Section: Introductionmentioning
confidence: 64%
“…The present study was designed to test the hypothesis that WPC supplementation can improve biomolecular damage, and restore the activity of membrane transporters during aging in rats. The present study is also important in view of our recent report of antiaging and neuroprotective effect of WPC in rat brain (Garg, Singh, Singh, & Rizvi, ).…”
Section: Introductionmentioning
confidence: 64%
“…Ebaid, Salem, Sayed, and Metwalli () stated that the administration of 0.1 g/kg of body weight of whey proteins to rats lowered several oxidative stress indicators such as MDA and NO. Also, Garg, Singh, Singh, and Rizvi () reported that WPC‐supplemented rats exhibited significant reduction in oxidative stress biomarkers levels.…”
Section: Discussionmentioning
confidence: 97%
“…28 Whey protein was also effective in reducing ROS and RNS production in aged rats and CCL 4 -induced rat hepatotoxicity through its metal-chelating activity. 15,30 In addition, WPC decreased the hepatic lipid peroxidation and DNA damage in rats treated with aflatoxin-B1, a hepatocarcinogenic mycotoxin. 31 The improvement of liver nonenzymic antioxidants shown in the current study in the DEN-treated mice by WPC may be due to its sulfur amino acids that enhanced the production of GSH.…”
Section: Discussionmentioning
confidence: 99%
“…They prevented free radicals from damaging cellular components (such as DNA, proteins, and lipids) by directly scavenging the free radicals and/or indirectly inhibiting the processes that produced free radicals . Whey protein was also effective in reducing ROS and RNS production in aged rats and CCL 4 ‐induced rat hepatotoxicity through its metal‐chelating activity . In addition, WPC decreased the hepatic lipid peroxidation and DNA damage in rats treated with aflatoxin‐B1, a hepatocarcinogenic mycotoxin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation